Community corrections in China: past development, current practices, and future challenges - Li, Spencer De (The Routledge handbook on global community corrections, 2024)
Since early 2000s, China has been building a community correction system to tackle prison overcrowding and high correctional cost while reducing recidivism and facilitating offender reintegration into the community. The central government has enacted laws and regulations to guide all community correction practices. However, since the system was an expansion of the pilot programs first implemented on the local levels, the structure and organization of the community correction agencies maintain considerable variation across jurisdictions although they all operate under the same legal framework and regulatory requirements. Despite all the problems and challenges it has faced, the system has grown rapidly and has achieved promising outcomes in a relatively short period of time. This article provides an overview of the development of community corrections in China and its major characteristics. The overview focuses on the rationale behind the correctional reform, its legal underpinning, its mission and objectives, organizational characteristics, staffing, supervision practices, and potential barriers to developing effective community correctional programs.